THE ROLE OF FAMILY AND SCHOOL PARTNERSHIP IN DEVELOPING FUNCTIONAL LITERACY IN STUDENTS - Mirzaliyeva Gulhayo Abdulazizovna (Innovate Conferences, 2025)
The article analyzes the role of family-school collaboration in developing functional literacy among primary school students. Effective practices such as family reading, project activities, and parent-teacher cooperation are examined.
Keywords: functional literacy, family-school cooperation, primary education, family reading, project activities, parental involvement, pedagogical partnership, education quality, student competencies, social skills.